A case study on cloud computing towards teaching and e-learning process among academicians in UiTM Segamat / Nur Khairunnisa Zamri...[et al.] - Zamri, Nur Khairunnisa; Sabtu, Rabiatul Adawiyah; Yahaya, Nor Izzurin; Abd Aziz, Basirah (2014)
Due to the advancement of technology, the teaching and learning process are required to do some of the transformation persistence to the infrastructure available nowadays. The existence of e-learning has grown into a widely accepted learning model due to its flexibility, diversity, measurement, opening and so on ,most of the colleges and universities offer courses through distance education or in online format as well as use various teaching and learning models now. There is a growing trend of using similar models for lifelong learning (Zheng He, 2012). Cloud computing is one of the tools that are frequently preferred by academicians recently as one of the storage medium in their teaching process. The purpose of this research is to see in the helicopter view pretending to the employment of cloud computing among the academicians in UiTM Segamat. The objectives of this study are to discover the awareness of e-learning using cloud computing and to explore the effectiveness of e-learning using cloud computing. By using a quantitative research, a survey questionnaire was used as the instrument and Systematic Random Techniques as the Sampling Techniques. The researcher is able to collect 88 percent of the distributed questionnaires from the respondents. Findings show that the case study on cloud computing towards teaching and learning process among academicians in UiTM Segamat does exist. Thus, this study proposed changes in technology, training, top management support, awareness in using cloud computing and institution support in cloud computing as the recommendation to the organization.